MbHY5-MbYSL7 mediates chlorophyll synthesis and iron transport under iron deficiency in Malus baccata - Sun, Yaqiang; Luo, Jiawei; Feng, Peien; Yang, Fan; Liu, Yunxiao; Liang, Jiakai; Wang, Hanyu; Zou, Yangjun; Ma, Fengwang; Zhao, Tao (Frontiers in Plant Science, 2022)
Iron (Fe) plays an important role in cellular respiration and catalytic reactions of metalloproteins in plants and animals. Plants maintain iron homeostasis through absorption, translocation, storage, and compartmentalization of iron via a cooperative regulative network. Here, we showed different physiological characteristics in the leaves and roots of Malus baccata under Fe sufficiency and Fe deficiency conditions and propose that MbHY5 (elongated hypocotyl 5), an important transcription factor for its function in photomorphogenesis, participated in Fe deficiency response both in the leaves and roots of M. baccata. The gene co-expression network showed that MbHY5 was involved in the regulation of chlorophyll synthesis and Fe transport pathway under Fe limiting conditions. Specifically, we found Fe deficiency induced the expression of MbYSL7 in root, which was positively regulated by MbHY5. Overexpressing or silencing MbYSL7 influenced the expression of MbHY5 in M. baccata.